WHAT DO THE PICTURES SAY IN A SCIENCE TEXTBOOK? - Nur'graha, Dhea Zakia Millah (2020)
Many studies have proven that images are essentials in learning science to help the learners understand the abstract scientific concept. Therefore, this study aims to investigate the use of images in a science textbook, by looking at the ideational meaning of the images and the captions accompanying them. By doing multimodal analysis, the study focuses on identifying the types of images and types of processes used in the images to find the ideational meaning. The data for this study are taken from the first six chapters in the Chemistry textbook used by IPSE students at UPI. The theory of reading images (Kress & Van Leeuwen, 2006) and Systemic Functional Grammar (Halliday, 1994) were used to analyze the visual and verbal modes in the textbook. The result of the analysis shows that ideationally, in terms of types of images, the textbook dominantly used realistic images, the one which represents reality in human viewpoint. In terms of types of processes, analytical images are dominantly used in the textbook. Ideationally, the visual and the verbal modes in the textbook are complementing each other to strengthen the meaning of the scientific concept that is being delivered to the learners. Thus, gleaned from the findings of the present research it can be said that the Chemistry textbook used by IPSE students is one of the example of a good textbook that can help the learners in understanding the scientific materials being delivered.